Factor V Leiden and Prothrombin Gene G 20210 A Variant in Children with Ischemic Stroke - Zenz, W.; Bodó, Z.; Plotho, Jutta; Streif, W.; Male, Ch.; Bernert, G.; Rauter, L.; Ebetsberger, G.; Kaltenbrunner, K.; Kurnik, P.; Lischka, A.; Paky, F.; Ploier, R.; Höfler, G.; Mannhalter, Christine; Muntean, W. (Thrombosis and Haemostasis, 1998)
Objective: To investigate if the factor V Leiden mutation (F-V-LM) and/or the prothrombin gene G 20210 A variant (P-G20210A-V) are risk factors for acute stroke in Austrian children. Patients: 33 children with acute ischemic stroke documented by computer tomography and/or magnetic resonance imaging of the brain were enrolled in an open multicenter survey. Results: 6/33 children had F-V-LM (5 heterozygous, 1 homozygous). This represents 18% (95% CI: 6.7-39.9%) of our pediatric stroke population and thus exceeds the expected prevalence in the Austrian population of 4,6% (Fischer’s exact test, p = 0.01). F-V-LM was not found in 11 children with neonatal stroke but in 6/22 children with stroke after the neonatal period. 5/6 children with F-V-LM had an underlying disorder that is a risk factor for stroke in children. The P-G20210A-V was detected in 1/26 (3.85%; 95% CI: 0.1-21.4%) patients. Comparison of the prevalence of P-G20210A-V in our study with that in the general population of Austria of 1% revealed no statistical significance (Fischer’s exact test, p = 0.38). Conclusion: Our data suggest that the F-V-LM is a risk factor for acute stroke in Austrian children beyond the neonatal period. The P-G20210A-V apparently does not represent a risk factor for stroke in Austrian children.